Profil supplementary scales Minnesota multiphasic personality inventory-2 (MMPI-2) adaptasi Indonesia pada komunitas public united not kingdom (punk) di kawasan Megamas Kota Manado - Ab'ror, Rijal; Kairupan, Bernabas H.R.; Munayang, Herdy (e-CliniC, 2016)
Abstract: Society in general still views punk community negatively. It is caused by their dress and hair styles which were assumed as weird, therefore, they are considered dangerous for other citizens. This study was aimed to examine mental health status of members of punk community for detection of the presence of any mental disorders. This was a survey study with a cross-sectional design to determine the members of punk community mental status at Megamas area in Manado based on Supplementary Scales of Minnesota Multiphasic Personality Inventory-2 (MMPI-2) Indonesian adaptation. According to socio-demographic data the majority of 30 respondents were males (86.67%), age range 18-27 years old (86.67%), respondentsâ€™ parents worked as private sectors employees (50%), respondents worked in private sectors (70%), had three siblings (43.33%), lived in Manado (76.67%), senior high school graduates (83.33%), reason of joining punk community was freedom (63,33%). Supplementary scales of MMPI-2 distribution obtained high t-score to low t-score as follows: PK (83.33%), AAS (56.67%), MAC-R (46.67%), A (46.67%), MDS (43.33%), Ho (36.67%), Mt (30%), OH (6.67%), R (3.33%), Es (0%), Do (0%), Re (0%), APS (0%), GM (0%), and GF (0%). Conclusion: The supplementary scales of MMPI-2 Indonesian adaptation in punk community at Megamas area in Manado city obtained high t-scores in Post Traumatic Disorder, Addiction Acknowledge/Admission Scale, MacAndrew Alcoholism-Revised, Anxiety Scale, Marital Distress, and Hostility Scales.Keywords: profile, supplementary scales, MMPI-2 Indonesian adaptation, punk communityÂ Abstrak: Masyarakat umumnya masih memandang komunitas punk dengan pandangan negatif dikarenakan gaya berpakaian dan gaya rambut yang aneh serta dianggap sebagai komunitas yang berbahaya. Penelitian ini bertujuan untuk mendapatkan status kesehatan mental pada anggota komunitas punk untuk mendeteksi adanya gangguan mental. Jenis penelitian ialah survey dengan desain potong lintang untuk mengetahui status mental anggota komunitas punk di kawasan Megamas Kota Manado berdasarkan Supplementary Scales Minnesota Multiphasic Personality Inventory-2 (MMPI-2) adaptasi Indonesia. Berdasarkan sosio-demografi dari 30 responden, distribusi anggota komunitas punk terbanyak ialah laki-laki (86,67%), rentang usia 18-27 tahun (86,67%), pekerjaan orang tua responden di bidang swasta (50%), pekerjaan responden di bidang swasta (70%), memiliki jumlah saudara sebanyak tiga orang (43,33%), beralamat di Kota Manado (76,67%), pendidikan terakhir SMA (83,33%), dan alasan bergabung pada komunitas punk karena menginginkan kebebasan (63,33%). Hasil distribusi supplementary scales MMPI-2, mendapatkan skala dengan t-skor yang tinggi dengan persentase berturut-turut dari tinggi ke rendah yaitu: PK (83,33%), AAS (56,67%), MAC-R (46,67%), A (46,67%), MDS (43,33%), Ho (36,67%), Mt (30%), OH (6,67%), R (3,33%), Es (0%), Do (0%), Re(0%),APS (0%), GM (0%), dan GF (0%). Simpulan: Supplementary Scales Minnesota Multiphasic Personality Inventory-2 (MMPI-2) adaptasi Indonesia yang tinggi yaitu pada Post Traumatic Disorder, Addiction Acknowledge/Admission Scale, MacAndrew Alkhoholism-Revised, Anxiety Scale, Marital Distress dan Hostility Scales. Kata kunci: profil, supplementary scales, MMPI-2 adaptasi indonesia, komunitas punk